An informed spatial filter for dereverberation in the spherical harmonic domain - Braun, Sebastian; Jarrett, Daniel; Fischer, Johannes; Habets, Emanuel (International Conference on Acoustics, Speech and Signal Processing, 2013)
In speech communication systems the received microphone signals are commonly degraded by reverberation and ambient noise that can decrease the fidelity and intelligibility of a desired speaker. Reverberation can be modeled as non-stationary diffuse sound which is not directly observable. In this work, we derive a multichannel Wiener filter in the spherical harmonic domain to reduce both reverberation and noise. The filter depends on the direction-of-arrival of the direct sound of the desired speaker and an interference power spectral density matrix for which an estimator is developed. The resulting informed spatial filter incorporates instantaneous information about the diffuseness of the sound field into the design of the filter. In addition, it is shown how the proposed filter relates to the well-known robust minimum variance distortionless response filter that is also used for comparison in the evaluation. Experimental results show that the proposed spatial filter provides a tradeoff between noise reduction and dereverberation depending on the diffuse sound PSD.